"Popcorn" Cavitary Pneumonia: A Case Report. Issue 5 (4th September 2020) - Bethuel, Nancy W.; Edmonds, Lee
Abstract : Upper lobe cavitation carries a broad differential. No review, to our knowledge, includes foreign body in the differential diagnosis. Similarly, reviews of foreign body aspiration do not report lung cavitation. Herein, we report a case of an alert 58-year-old man who presented with sepsis secondary to presumed right upper lobe pneumonia. Computed tomography of the chest was significant for multiple loculated cavitary lesions. Subsequent bronchoscopy revealed a single kernel of popcorn impacted in the bronchus. Our case report highlights the importance of recognizing atypical presentations of foreign body aspiration.